The Emotional Intelligence of Japanese Mental Health Nurses - Ishii, Shinichiro; Horikawa, Etsuo (Frontiers in Psychology, 2019)
The aim of this study was to measure emotional intelligence in nurses in Japan, and to elucidate the characteristics of mental health nurses. Anonymous, self-administered questionnaires were distributed to 206 nurses working in three psychiatric hospitals and two internal medicine hospitals in Japan. The number of participants included in the analysis was 159 (valid response rate, 77.2%), of which 87 were mental health nurses. Emotional intelligence was measured using the Japanese version of the Wong and Law Emotional Intelligence Scale. In the analysis, the emotional intelligence of mental health nurses and internal medicine nurses was compared using a t-test. The results of a t-test comparing emotional intelligence scale scores between the mental health nurses and internal medicine nurses showed that the total mean score and Self-Emotions Appraisal score were significantly lower in mental health nurses than in internal medicine nurses. The self-awareness of mental health nurses was significantly lower than that of nurses in other fields (P<0.001, Cohen’s d: 0.65). The results of this study provide a basis for future research on the emotional intelligence of nurses in Japan. Development of an emotional intelligence scale based on the characteristics of Japanese nurses will be important regarding nurses’ assessment of their own emotions and the emotions of others. The kinds of people nurses are involved with and the content of their support for others also need to be clarified.